Self-management and leadership development - Rothstein, Mitchell G.; Burke, Ronald J. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2010)
This book is important, timely and relevant because it brings together sources on the self management of leadership development which relies on the leaders capability to manage his/her personal development. It touches on the instrumental role played by individuals in managing their own development, rather than depending on others, such as their organisation, to guide them.
Includes bibliographical references and index.
uaj 10/05/13
Loan
Keywords: Leadership; Self-management (Psychology); Leadership - development